2014
DOI: 10.4049/jimmunol.1302822
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mouse and Human Autophagy Proteins in IFN-γ–Induced Cell-Autonomous Responses against Toxoplasma gondii

Abstract: IFN-γ mediates cellular innate immunity against an intracellular parasite, Toxoplasma gondii, by inducing immunity-related GTPases such as p47 IFN-γ–regulated GTPases (IRGs) and p65 guanylate-binding proteins (GBPs), which also participate in antibacterial responses via autophagy. An essential autophagy protein, Atg5, was previously shown to play a critical role in anti–T. gondii cell-autonomous immunity. However, the involvement of other autophagy proteins remains unknown. In this study, we show that essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
130
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(136 citation statements)
references
References 44 publications
6
130
0
Order By: Relevance
“…This is similar to the effect seen with T. gondii, in which basal autophagy is subverted by the parasite for its own growth (33), whereas the parasite can be eliminated by induced autophagy/autophagy-related process in response to IFN-γ (12,(34)(35)(36)(37). Also note that in this study we observed only roughly one-half of the rescue activity with the reduction in Beclin 1 or ATG5 expression and PI3K activity, and thus the contribution of additional factors leading to liver-stage P. vivax elimination remain to be identified.…”
Section: Liver-stage P Vivax Colocalizes With Lc3 and Ltrsupporting
confidence: 67%
“…This is similar to the effect seen with T. gondii, in which basal autophagy is subverted by the parasite for its own growth (33), whereas the parasite can be eliminated by induced autophagy/autophagy-related process in response to IFN-γ (12,(34)(35)(36)(37). Also note that in this study we observed only roughly one-half of the rescue activity with the reduction in Beclin 1 or ATG5 expression and PI3K activity, and thus the contribution of additional factors leading to liver-stage P. vivax elimination remain to be identified.…”
Section: Liver-stage P Vivax Colocalizes With Lc3 and Ltrsupporting
confidence: 67%
“…S10). GBP translocation to T. gondii PVs and C. trachomatis inclusions has also been observed in humans cells (48,49), yet human cells do not encode GKS proteins (20). These combined observations pose the conundrum of explaining how human GBPs target PVs independently of GKS proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Interference with ATG8 lipidation diminishes GBP and GKS protein recruitment to PVs, demonstrating the importance of these molecules in immunotargeting of PVs (24,25,42,48,(55)(56)(57). Whether and how the ATG8 pathway intersects with the newly discovered IRG-driven ubiquitination pathway will need to be explored further in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of hGBPs to the membranes of T. gondii-containing PVs is regulated by the autophagic protein, ATG16L1, in IFN-γ-stimulated human fibroblast-like (HAP1) cells (45). Here, using both the noncyst and cyst-forming strains (RH/GFP and PLK/ RED) of T. gondii (46), we observed the recruitment of endogenous hGBP1 to T. gondii-containing PVs at 3 h postinfection in IFN-γ-stimulated human MSCs (Fig.…”
Section: Discussionmentioning
confidence: 99%